Die Nederlandse Geloofsbelydenis en drie besondere ampte: Artikel 30 "n verstarring? - Strauss, Piet J. (HTS teologiese studies, 2023)
The Confessio Belgica and the three offices: Article 30 inflexible? The Confessio Belgica or Dutch Confession of Faith from 1561, one of the Three Formulas of Unity in the Dutch Reformed tradition, confesses in article 30 that the government of the church, as an institution of the Christian faith, should be spiritual and conducted by chosen consistories. These consistories should consist of ministers, elders and deacons. The norm or constant of three offices was excepted by churches in this tradition, but more recently it’s necessity and efficiency became questioned in some of these circles. Historically the three offices served the Reformed churches well. The acceptance of the three offices is based on the Confessio Belgica as a confession, but also on the biblical principle that Christ is the head of the church and its highest Prophet, eternal King and only Priest. The church grows spiritually out of Christ and his Spirit as their head. In this process, the church also uses the offices of minister, elder and deacon as instruments. These offices correspond with the offices of Christ as their Prophet, King and Priest. A study of the Confessio Belgica article 30 leads to the belief that it does not exclude changes in the task of the three offices nor opposes the addition of extra offices or the help of additional functionaries.Contribution: This article contributes theologically to the debate in the Dutch [Netherlands] Reformed churches on the offices in church. It tries to clarify all the thinking regarding the impact of the reformed Three Formulas of Unity, and especially the Dutch Confession of Faith article 30 on the work or service of the church and norms or principles to achieve an acceptable functioning of the offices in church. The solution aims at stability and new initiatives on the offices in church.